2009
DOI: 10.1002/j.2161-1882.2009.tb00039.x
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Link Between Self‐Construal and Distress Among African American and Asian American College Students

Abstract: The authors investigated ethnicity, self‐construal, and distress among African American and Asian American college students. African American students expressed more salient independent self‐construals, whereas Asian American students expressed more salient interdependent self‐construals. As hypothesized, among African American participants, distress was positively related to interdependent self‐construal and negatively associated with independent self‐construal. Contrary to prediction, the same pattern was fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 41 publications
0
14
0
Order By: Relevance
“…A higher score indicates higher psychological distress. The coefficient alpha was .86 among Asian American students (Christopher & Skillman, 2009) and .90 for our participants. Construct validity of this scale was supported by a negative association with positive affect and a positive association with negative affect among Asian American college students (Lee, Su, & Yoshida, 2005).…”
Section: Methodsmentioning
confidence: 60%
“…A higher score indicates higher psychological distress. The coefficient alpha was .86 among Asian American students (Christopher & Skillman, 2009) and .90 for our participants. Construct validity of this scale was supported by a negative association with positive affect and a positive association with negative affect among Asian American college students (Lee, Su, & Yoshida, 2005).…”
Section: Methodsmentioning
confidence: 60%
“…Steele ( 63 ) discovered that being under threat of judgement by a racial stereotype leads to impaired performance on tests and is associated with lower levels of mental well-being. Other research suggests that ethnic minority students might experience low levels of mental well-being and higher levels of mental illness because of the university campus climate or existing institutional prejudice and discrimination ( 64 67 ). In a study of first year medical students Hardeman et al ( 9 ) compared African American students to white students and found that African American students had nearly twice the risk of being classified as having symptoms of depression and anxiety.…”
Section: Predicting Student Mental Well-beingmentioning
confidence: 99%
“…College students. In a study based on college students, Christopher and Skillman (2009) examined the relationship between self-construal and ethnicity among Asian Americans and African Americans. The results showed that Asian Americans had greater levels of interdependent self-construal whereas African American students had higher levels of independent self-construal.…”
Section: Elementary School Studentsmentioning
confidence: 99%